Spatiotemporal regulation of alginate sub-structures at multiple scales revealed by monoclonal antibodies - Catherine T. Jones; Cassie Bakshani; Ieva Lelenaite; Jozef Mravec; Stjepan Krešimir Kračun; Jeff Pearson; Mathew D. Wilcox; Kevin Hardouin; Sonia Kridi; Cécile Hervé; William G.T. Willats (The Cell Surface)
Alginates are abundant linear polysaccharides produced by brown algae and some bacteria. They have multiple biological roles and important medical and commercial uses. Alginates are comprised of D-mannuronic acid (M) and L-guluronic acid (G) and the ratios and distribution patterns of M and G profoundly impact their physiological and rheological properties. The structure/function relationships of alginates have been extensively studied in vitro but our understanding of the in vivo spatiotemporal regulation of alginate fine structures and their biological implications is limited. Monoclonal antibodies (mAbs) are powerful tools for localising and quantifying glycan structures and several alginate-directed mAbs have been developed. We used a library of well-defined alginates, with M and G block ratios determined by NMR, to refine our understanding of the binding properties of alginate-directed mAbs. Using these probes, we obtained new insight into how structural features of alginates are regulated at different scales, from cellular to seasonal.